AN INTERVIEW WITH CAROL S. LIDZ: ASSESSMENT AND GIFTED - Shaughnessy, Michael (Acta Scientiae et Intellectus, 2024)
Carol S. Lidz worked in a variety of settings as a school psychologist for forty years. She is a graduate of University of Michigan (B.A., Psychology), University of Tennessee, (M.A.,School Psychology), and Rutgers University-Graduate School of Applied Professional Psychology, Psy.D.). She has held faculty positions in school psychology at Temple University, where she directed the Early Childhood Specialization for School Psychologists program, and the Graduate School of Education and Psychology of Touro College, where she designed and directed the school psychology program. Just prior to her retirement, she joined Freidman Associates, where she provided school neuropsychological assessments of children with learning disorders. She is the author of a number of books, chapters, and articles on dynamic assessment and assessment of preschool children. Her most recent books include Early Childhood Assessment, published by Wiley in 2003, and Dynamic Assessment in Practice: Implications for Clinical and Educational Settings, co-authored with H. Carl Haywood, published by Cambridge University Press in 2007.